PRESTASI BELAJAR FIQH DITINJAU DARI MINAT DAN GAYA BELAJAR PADA SISWA MADRASAH DINIYYAH NURUL UMMAH PUTRI TAHUN 2016/2017 - Eva Latipah; Khusnul Khotimah (Jurnal Pendidikan Agama Islam)
Subject of fiqh is one of compulsory subjects at level of Madrasah Ibtidaiyyah (MI) education. Therefore, having a high learning achievement in the course of fiqh is very important. This study aims to examine correlation between interest and learning styles with fiqh learning achievement.